Easy World Wide Web with Netscape - Minatel, Jim (Que, 1995)
"Save time and effort - discover the fastest, easiest way to get up to speed with Netscape for the World Wide Web. Easy World Wide Web with Netscape shows you all the essentials in full color, so you can cruise the Web quickly, easily, and with minimum effort."--BOOK JACKET. "This fully illustrated, step-by-step guide uses a proven approach to learning the basics. Just follow the simple directions, watch the tasks unfold on sample screen pictures, and then do it yourself!"--BOOK JACKET. "Step-by-step lessons show you how to get up and running with Netscape, learn how to cruise the Web, find your favorite pages quickly using Bookmarks, and view pictures, listen to sound clips, and play multimedia files."--BOOK JACKET.